Implementasi Pembelajaran Daring Pada Masa Pandemi Corona Virus Disease 19 (COVID-19) - Prasetio, Tri Agung (Prosiding University Research Colloquium, 2021)
This study aims to determine the implementation of online learning during the coronavirus disease 19 (Covid-19) pandemic which was carried out at SD Negeri Paremono 1 Mungkid. The subjects of this study were selected by purposive sampling. Data collection techniques were carried out by observation, interviews, and documentation. research informants are teachers, students, parents. Test the validity of the data using triangulation of sources, times, and methods. The data analysis used is the Miles and Huberman model, namely data reduction, data presentation and data conclusion/verification. The results of the study can be concluded that (1) The implementation of online learning by teachers uses 2 learning systems, namely online and home visits. teachers use technology as online learning media such as whatsapp, youtube and google form (2) Supporting and inhibiting factors for the implementation of online learning are: a) supporting factors, namely support for infrastructure such as cellphones, laptops, and internet quotas and stable networks in schools. Good mood of students in participating in online learning, as well as guidance and assistance of parents in student learning. b) The inhibiting factor is the limited time in the delivery of learning material so that the material is not delivered optimally. Some students experience internet network problems so that they are not on time in participating in learning. Students who feel bored in participating in online learning so that students are even engrossed in playing games on their cellphones. The inhibiting factor experienced by parents is time and lack of understanding of Information Technology (IT) so that it is difficult to guide students.